2021
DOI: 10.3390/toxins13090600
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of an LC-MS/MS Based Method for the Determination of Deoxynivalenol and Its Modified Forms in Maize

Abstract: The Fusarium mycotoxin deoxynivalenol (DON) is a common contaminant of cereals and is often co-occurring with its modified forms DON-3-glucoside (D3G), 3-acetyl-DON (3ADON) or 15-acetyl-DON (15ADON). A stable-isotope dilution liquid chromatography-tandem mass spectrometry (LC-MS/MS) based method for their determination in cereals was developed and validated for maize. Therefore, 13C-labelled D3G was enzymatically produced using 13C-DON and [13C6Glc]-sucrose and used as an internal standard (IS) for D3G, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…F. solani can metabolize and produce trichothecene, 15-ADON, as one kind of type B trichothecene, was detected in A. sinensis fusarium rot lesions caused by F. solani . 15-ADON has various toxic effects, including anorexia, growth retardation, immunotoxicity, and impaired reproduction [ 40 ], posing a serious threat to human health. There are previous reports of 15-ADON contamination in Fusarium species-infested wheat spikes [ 41 ] and maize [ 42 ], but no report in Chinese herbs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…F. solani can metabolize and produce trichothecene, 15-ADON, as one kind of type B trichothecene, was detected in A. sinensis fusarium rot lesions caused by F. solani . 15-ADON has various toxic effects, including anorexia, growth retardation, immunotoxicity, and impaired reproduction [ 40 ], posing a serious threat to human health. There are previous reports of 15-ADON contamination in Fusarium species-infested wheat spikes [ 41 ] and maize [ 42 ], but no report in Chinese herbs.…”
Section: Discussionmentioning
confidence: 99%
“…Mycotoxins are secondary metabolites of pathogenic molds produced under favorable conditions, having carcinogenic, teratogenic, or mutagenic effects on human health [ 40 ]. The results in the present study showed that 2 mg L −1 ozone treatment significantly reduced the mycotoxin accumulation in diseased A. sinensis tissues, and 2 h ozone exposure was more effective than the 1 h ozone exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The presence was detected with a stable-isotope dilution liquid chromatography–tandem mass spectrometry-based approach that relies on labeling of toxins enzymatic byproducts with 13C. The method efficiently detected D3G (76–98%), DON (86–103%), 15ADON (68–100%), and 3ADON (63–96%) . Zhang et al employed ultrahigh-performance liquid chromatography–HRMS to detect 82 mycotoxins and categorize into 8 classes by Python program developed with “Fragmentation pattern screener (FPScreener)” and nontarget screening rules.…”
Section: Current Challenges and Future Prospectsmentioning
confidence: 99%
“…Masked mycotoxins have been detected in extractable conjugated and nonextractable varieties (usually to unavailability of toxins in extracted samples, bound mycotoxins are not accessible for analysis and need chemical or enzymatic treatment prior detection). 238 Fiby et al 239 reported the presence of Fusarium mycotoxin like deoxynivalenol in native as well as masked form (DON-3glucoside "D3G", 3-acetyl-DON "3ADON", or 15-acetyl-DON "15ADON") in cereals. The presence was detected with a stableisotope dilution liquid chromatography−tandem mass spectrometry-based approach that relies on labeling of toxins enzymatic byproducts with 13C.…”
Section: Low Concentrationmentioning
confidence: 99%
See 1 more Smart Citation